Sympathetic Neural Overdrive, Aortic Stiffening, Endothelial Dysfunction, and Impaired Exercise Capacity in Severe COVID-19 Survivors: A Mid-Term Study of Cardiovascular Sequelae. Issue 2 (23rd November 2022) - Faria, Diego; Moll-Bernardes, Renata J.; Testa, Laura; Moniz, Camila M.V.; Rodrigues, Erika C.; Rodrigues, Amanda G.; Araujo, Amanda; Alves, Maria J.N.N.; Ono, Bruna E.; Izaias, João E.; Salemi, Vera M.C.; Jordão, Camila P.; et al.
Abstract : Background: COVID-19 has become a dramatic health problem during this century. In addition to high mortality rate, COVID-19 survivors are at increased risk for cardiovascular diseases 1-year after infection. Explanations for these manifestations are still unclear but can involve a constellation of biological alterations. We hypothesized that COVID-19 survivors compared with controls exhibit sympathetic overdrive, vascular dysfunction, cardiac morpho-functional changes, impaired exercise capacity, and increased oxidative stress. Methods: Nineteen severe COVID-19 survivors and 19 well-matched controls completed the study. Muscle sympathetic nerve activity (microneurography), brachial artery flow-mediated dilation and blood flow (Doppler-Ultrasound), carotid-femoral pulse wave velocity (Complior), cardiac morpho-functional parameters (echocardiography), peak oxygen uptake (cardiopulmonary exercise testing), and oxidative stress were measured ~3 months after hospital discharge. Complementary experiments were conducted on human umbilical vein endothelial cells cultured with plasma samples from subjects. Results: Muscle sympathetic nerve activity and carotid-femoral pulse wave velocity were greater and brachial artery flow-mediated dilation, brachial artery blood flow, E/e′ ratio, and peak oxygen uptake were lower in COVID-19 survivors than in controls. COVID-19 survivors had lower circulating antioxidant markers compared with controls, but there were no differences in plasma-treated human umbilical vein endothelial cells nitric oxide production and reactive oxygen species bioactivity. Diminished peak oxygen uptake was associated with sympathetic overdrive, vascular dysfunction, and reduced diastolic function in COVID-19 survivors. Conclusions: Our study revealed that COVID-19 survivors have sympathetic overactivation, vascular dysfunction, cardiac morpho-functional changes, and reduced exercise capacity. These findings indicate the need for further investigation to determine whether these manifestations are persistent longer-term and their impact on the cardiovascular health of COVID-19 survivors.